SPE-HPLC-DAD Dosage of Seven Neonicotinoids in Green Coffee - Serenella Seccia; Stefania Albrizio; Irene Dini (Molecules)
Green coffee is essential in many tropical economies. Its cultivation often necessitates using pesticides that can leave behind residues harmful to human health. To ensure consumer safety, the European Community has set strict maximum residue limits (ranging from 0.01 to 1.0 mg/kg) for pesticides in green coffee sold within Europe. However, the lack of official testing methods for neonicotinoids (NEOs) is a problem, as laboratories must spend resources and time developing and validating suitable analytical methods. This study developed and validated a method for the simultaneous analysis of seven NEOs frequently used in coffee cultivation: acetamiprid, clothianidin, dinotefuran, imidacloprid, nitenpyram, thiacloprid, and thiamethoxam. The proposed methodology uses Strata®-X PRO cartridges (solid-phase extraction) to remove interfering compounds present in the food matrix and high-performance liquid chromatography (HPLC), equipped with a diode array detector (DAD), to determine NEOs. The accuracy profile strategy validated the method’s suitability for the intended application. NEO recovery rates above 97%; negligible matrix effects (>93%); the linearity of the quantification method (R2 values above 0.99); relative biases and standard deviations below 5% and 6%, respectively; and an expected error rate less than 8% allowed to consider the method reliable for the intended objectives. Because of its low ecological impact and simple execution, this method can be used in routine analyses.